Key performance indicators : developing, implementing, and using winning KPIs - Parmenter, David (Hoboken, N.J. : John Wiley & Sons, 2010)
'Fully revised and updated, Key Performance Indicators: Developing, Implementing, and Using Winning KPIs, Second Edition represents a significant shift in the way KPIs are developed and used, with an abundance of implementation tools.'--BOOK JACKET
Introduction -- Foundation stones for implementing key performance indicators -- Developing and using KPIs : a 12-step model -- KPI team resource kit -- Templates for reporting performance measures -- Facilitator's resource kit -- Critical success factors kit -- Brainstorming performance measures -- Implementation variations for small-to-medium enterprises and not-for-profit organizations -- Implementation lessons
Includes bibliographical references and index
Keywords: Performance technology; Performance standards; Organizational effectiveness